Depressive symptoms in high-performance athletes and non-athletes: a comparative meta-analysis - Gorczynski, P. F.; Coyle, M.; Gibson, K. (2017)
Objective: To assess whether a difference exists in prevalence of mild or more severe depressive symptoms between high-performance athletes and non-athletes. Design: Comparative odds-ratio meta-analysis. Data sources: We searched PSYCHINFO, PUBMED, MEDLINE, CINHAL, SPORTDiscus, and Google Scholar as well as the reference lists of reviews of mental health issues in high-performance athletes. Eligibility: We included studies that compared high-performance athletes and non-athletes, included a validated measure of depressive symptoms, and included the prevalence of individuals who indicated at least mild depressive symptoms. Results: Five articles reporting data from 1545 high-performance athletes and 1811 non-athletes were examined. A comparative odds-ratio meta-analysis found high-performance athletes were no more likely than non-athletes to report mild or more severe depressive symptoms (OR=1.15, 95% CI=.954, 1.383, p=.145). Male high-performance athletes (n=940) were no more likely than male non-athletes (n=605) to report mild or more severe depressive symptoms (OR=1.17, 95% CI=.839, 1.616, p=.362). For females, high-performance athletes (n=948) were no more likely than non-athletes (n=605) to report mild or more severe depressive symptoms (OR=1.11, 95% CI=.846, 1.442, p=.464). Overall, male high-performance athletes (n=874) were 52% less likely to report mild or more severe depressive symptoms than female high-performance athletes (n=705) (OR=.48, 95% CI=.369, .621, p<.001). Summary/conclusions: High-performance athletes were just as likely as non-athletes to report depressive symptoms. Researchers need to move beyond self-report measures of depressive symptoms and examine the prevalence of clinically diagnosed depressive disorders in athletes.